A Model Of Quality Management Development In Islamic Educational Institutions - Edy, Sarwo (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
It is undeniable that management aspects have a significant influence on the expedition of an institution. This is because management is related to shrewdness in designing activities, implementing them as well as possible, supervising activities evenly so that planned activities can run well, the purpose of this research is to find out how the management model is in an Islamic educational institution. improve the quality of institutions, and this research uses a qualitative approach with case studies on one problem, namely the quality development model in Islamic education institutions, and the method used is qualitative with a case study approach and the findings in this study are the results of in-depth interviews with informants, then make observations in informant interaction activities with the environment to find the necessary data and conduct documentation studies. The description of the research results is in the form of a description based on information obtained from the main informants and basic informants. The results of in-depth research from informants The management development model is strongly influenced by how a manager manages an educational institution, how he makes decisions, makes policies and develops the quality of employee/teacher performance to create other programs within the institution, whose goal is none other than to improve the quality of educational institutions self.